Factors Involved in Missed Nursing Care: A Systematic Review - Monalisa Monalisa; Mohd Syukri; Yellyanda Yellyanda; Bettywati Eliezer T (Iran University of Medical Sciences, 2023)
Background: Missed nursing care (MNC) is experienced in nearly all healthcare facilities. Awareness of the aspects involved in the MNC can improve the quality of patient care. The objective of this systematic review is to provide insights into the factors that contribute to the occurrence of MNC. Methods: The review will adhere to the 2020 preferred reporting items for systematic review and meta-analyses (PRISMA) statement and includes studies published in peer-reviewed journals from 2012 to 2022. The databases used in the literature search include ScienceDirect, Cochrane Library, PubMed, ProQuest, and the Wiley Online Library. The eligibility criteria were determined based on population, intervention, comparison, outcomes, and study (PICOS) guidelines. To evaluate the quality of the studies, the NIH quality assessment tool for observational cohort and cross-sectional studies was employed, while the risk of bias was assessed using the Cochrane collaboration's risk of bias tool. Three authors independently performed data extraction using qualitative analysis and reached a final agreement. Results: A total of 3611 articles were found in the database search. After removing duplicates and ineligible articles, review studies, case reports, letters to editors, incomplete texts, dissertations, and book chapters, 16 articles were finally eligible for further analysis. In general, there were three categories of factors related to MNC, including labor resources (workload, staff adequacy, staff characteristics, nurse-patient ratio, shift work, and nurse job satisfaction), material sources (work environment, personal protective equipment, patient care equipment), and teamwork and communication (communication within nursing team, and communication with medical staff). The most common influencing factor seemed to be staffing adequacy.  Conclusion: The role of healthcare service management and leadership is central to mitigating the factors contributing to MNCs' emergence, especially labor resources. Meta-analytic studies are needed to find the most influential factors of MNC based on the results of all available studies.